2014
DOI: 10.3109/01913123.2014.933289
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Curcumin on Hepatotoxicity and Ultrastructural Damage Induced by Cisplatin

Abstract: We investigate the protective effect of curcumin (CU) on the hepatic ultrastructural damage induced by cisplatin in mice. 18 adult Kunming mice were randomly divided into normal saline (NS) group, cisplatin treatment group (CP) and CU + CP group (n = 6 for each group). Mice in control group and CP group were administered with NS (20 mL/kg/day) and CU + CP group were i.p injected with CU (200 mg/kg/day) for 10 days. Then cisplatin (50 mg/kg/day) was injected in mice of CP group and CU + CP group, while those in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
0
16
0
3
Order By: Relevance
“…They also found that pretreatment of curcumin prior to cisplatin could prevent cisplatin-induced hepatotoxicity in rat model ( Waseem et al, 2014 ). Wang et al (2014) investigated the effect of curcumin on cisplatin-induced hepatotoxicity and ultrastructural damage. Their results showed that cisplatin had significant liver damage with vacuolated cytoplasm and blurred trabecular structure after cisplatin (50 mg/kg/day) was injected via i.p to Kunming mice for 10 days, and curcumin treatment (200 mg/kg/day) for 10 days could prevent cisplatin-induced liver damage ( Wang et al, 2014 ).…”
Section: The Preventive Effects Of Curcumin Against Chemotherapy-indumentioning
confidence: 99%
“…They also found that pretreatment of curcumin prior to cisplatin could prevent cisplatin-induced hepatotoxicity in rat model ( Waseem et al, 2014 ). Wang et al (2014) investigated the effect of curcumin on cisplatin-induced hepatotoxicity and ultrastructural damage. Their results showed that cisplatin had significant liver damage with vacuolated cytoplasm and blurred trabecular structure after cisplatin (50 mg/kg/day) was injected via i.p to Kunming mice for 10 days, and curcumin treatment (200 mg/kg/day) for 10 days could prevent cisplatin-induced liver damage ( Wang et al, 2014 ).…”
Section: The Preventive Effects Of Curcumin Against Chemotherapy-indumentioning
confidence: 99%
“…Therefore, we and others have shown that the use of natural molecules such as polyphenols can modulate xenobiotic-metabolizing enzymes as well as the pathways leading to cancer cell death, making it possible to restore sensitization to anticancer agents. For example, resveratrol, curcumin, vitamin E, and gallic acid are able to protect cells from cisplatin-induced genotoxicity [13][14][15]. Very interestingly, some of these natural compounds are able to synergize at the same time with various anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor sections were collected and fixed in 4% paraformaldehyde. Paraffin-embedded tissue sections (5 mm) were stained with H&E, according to standard techniques (35). Images were captured using a Nikon Eclipse Ci light microscope (Nikon Instruments, Inc., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were dehydrated in a graded ethanol series, embedded in Epon 812 (SPI Supplies/Structure Probe, Inc., West Chester, PA, USA). The sections were examined under by transmission electron microscopy (35).…”
Section: Methodsmentioning
confidence: 99%